Mild temperatures differentiate while extreme temperatures unify gene expression profiles among populations of Dicosmoecus gilvipes in California - King, Emily E.; Stillman, Jonathon H. (Frontiers in Physiology, 2022)
Accurately predicting the effects of future warming on aquatic ectotherms requires an understanding how thermal history, including average temperature and variation, affects populations of the same species. However, many laboratory studies simplify the thermal environment to focus on specific organismal responses and sacrifice environmental realism. Here, we paired laboratory-based transcriptomic RNA-seq analysis to identify thermally responsive genes with NanoString analysis of a subset of those genes to characterize natural field-based variation in thermal physiology among populations. We tested gene expression responses of three populations of field-acclimatized larval caddisflies (Dicosmoecus gilvipes) from streams in different eco-regions (mountain, valley, and coast) following exposure to current and future summertime temperatures. We hypothesized that distinct thermal histories across eco-regions could differentiate populations at baseline “control” levels of gene expression, as well as gene expression changes in response to daily warming and heat shock. Population-specific patterns of gene expression were apparent under the control and daily warming conditions suggesting that local acclimatization or local adaptation may differentiate populations, while responses to extreme temperatures were similar across populations, indicating that response to thermal stress is canalized. Underlying gene co-expression patterns in the daily warming and heat shock treatments were different, demonstrating the distinct physiological mechanisms involved with thermal acclimatization and response to thermal stress. These results highlight the importance and limitations of studies of the thermal biology of wild-caught organisms in their natural environment, and provide an important resource for researchers of caddisflies and aquatic insects in general.